(untitled) (Research, Society and Development, 2022)
The growing search for a sustainable lifestyle, increases the demand for materials that are meeting environmental issues, which are technically and economically viable. Soil-cement products cover all these mentioned aspects. The objective of this work is to verify a superior performance between curing methods, studying their influence on the simple compressive strength and on the water absorption of soil-cement specimens. A standard composition, 90% soil and 10% cement, was used. Molding moisture was obtained using the normal Proctor test, with a result of 18.6%. After molding, the specimens were subjected to curing by manual spraying, curing by water slide and without curing, for comparative purposes, followed by tests. The results indicate the curing by water layer with superior results, with an average of simple compressive strength of approximately 5.20 MPa and water absorption of 12.97%.